Effect of Socio-Economic Characteristics and Cultural Areas on the Educated Poor in East Java Province - Agus Dian Ristanto; Candra Fajri Ananda; Farah Wulandari Pangestuty (Journal of International Conference Proceedings, 2022)
Education is one way to save oneself from poverty. There are 19.5 percent of poor people in East Java who have completed education at the senior high school level and above but are still in poor condition. This study aims to examine the effect of socio-economic and regional characteristics on the status of the poor with upper secondary education in each cultural area in the province of East Java. Using the 2021 Susenas data which was analyzed with binary logistic regression, it was found that there were differences in socio-economic characteristics in each cultural area. Disability disorders and gender affect educated poverty in the Arek area but have no effect in the Pandalungan, Mataraman, and Madura Islands areas. Formal and informal sector jobs only have an effect in the Pandalungan area and have no effect in other areas. Choosing to work in the primary sector only affects the Mataraman area. While the factors of age, access to technology and use of the internet reduce the opportunities for poverty in all cultural areas.Â Keywords: Poverty, Logistic Regression, Susenas, educated poor, cultural area